PENERAPAN METODE HYPNOTEACHING DALAM UPAYA PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA - Restu Banu Aji; Uba Umbara; Ricky Yuliardi (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
Application of Hypnoteaching Method to imrove Communication Skills Mathematical Student. This study aims to determine students’ mathematical communication skills before and after learning mathematical with Hypnoteaching Method. Pretest data analysis results obtained value tcount = −1, 26 , while at the 0,05 significance level and 40 degrees of freedom, obtained value t(0,975)(40) = 0,021 because -2,021 < -1,26 < 2,021 or − < < t t t table count table then Ho is accepted, it means not different as significance between mathematical communication skills early experimental class and mathematical communication skills early control class. While the posttest analysis result obtained value tcount = 2,632 , while at the 0,05 significance level and 40 degrees of freedom, obtained value t(0,95)(40) =1,684 because 2,632 > 1,684 or t t count table > then H1 is accepted, it the ability of students mathematical communication use Hypnoteaching method is better than students mathematical communication who use conventional learning. In addition, the result of the test analysis gain obtained zcount = −6,7 and z z table = = 0,45 1,64 . Because -6,7 < 1,64 then H0 is accepted and it means the experimental students’ ability of mathematical communication isn’t on the high level. In addition, from the result of attitude scale, it is known that the student showed a positive response to Hypnoteaching Method.